Hubungan Karakteristik Pasien Terhadap Kepatuhan Penggunaan Antidiabetes Oral di Posyandu Lansia Desa Paulan Colomadu Karanganyar - Cindy, Granada; Hartono, H (Indonesian Journal on Medical Science, 2024)
Diabetes Mellitus is a disease with metabolic disorders whose population continues to increase every year. Compliance is a change in behavior according to the orders given. The level of adherence is low and affects the success of the therapy carried out. This study was conducted to determine whether there is a relationship between patient characteristics and adherence in taking oral anti-diabetic drugs in type-2 diabetes mellitus patients. The research was conducted at the Elderly Posyandu in Paulan Colomadu Village, Karanganyar in December 2022. The type of research used was cross-sectional analysis, that is, directly collecting independent related variables at once. The data collection instrument used the Medication Adherence Report Scale Questionnaire (MARS-5). Data analysis was performed using SPSS version 26 with a chi-square test analysis with a significance of 95% (a = 0.05). Patients at the Elderly Posyandu in Paulan Colomadu Village aged 45-59 years 49.1%, aged > 60 years 50.9%, female 78.9%, male 21.1%, education ? SMA 73.7%, > SMA 26.3%, not working 57.9%, working 42.1%, duration of suffering <1 year 21.1%, ?1 year 78.9%, patients without other diseases 63.2%, with other diseases 36, 8%. Patients taking a single drug 61.4% and 38.6% combination drug. Treatment of patients without family motivation 86%, with 14% family motivation. The results of the study proved that 52.63% of elderly patients were adherent in using oral anti-diabetes drugs and 47.37% of patients were non-adherent in using drugs. The chi-square test with a significance of 95% showed that there was no relationship between gender, occupation, other illnesses and motivation on adherence to oral anti-diabetic use, but there was a relationship between age, education, duration of diabetes mellitus, and the number of drugs consumed on adherence to use. oral antidiabetics.